2021
DOI: 10.21873/invivo.12625
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene Receptor Antagonist Use and Dementia Risk in Patients With Asthma: A Retrospective Cohort Study

Abstract: Background/Aim: Recent experimental studies have reported that leukotriene receptor antagonists (LTRAs) might protect against dementia. However, few clinical studies have examined this in humans. This study assessed whether the use of LTRAs can prevent the onset of dementia in humans. Patients and Methods: A large population-based retrospective cohort study was conducted using a health insurance claims database in Japan, which included patients newly diagnosed with bronchial asthma between 2006 and 2015. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
1
7
0
2
Order By: Relevance
“…30 In a small cohort of asthma patients, leukotriene receptor antagonists decreased risk of dementia. 31 Third, allergy may induce vascular pathology and cerebrovascular dysfunction. In many previous studies, allergic diseases were associated with hypertension, diabetes, atherosclerosis, and cardiovascular and cerebrovascular diseases-established risk factors for dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In a small cohort of asthma patients, leukotriene receptor antagonists decreased risk of dementia. 31 Third, allergy may induce vascular pathology and cerebrovascular dysfunction. In many previous studies, allergic diseases were associated with hypertension, diabetes, atherosclerosis, and cardiovascular and cerebrovascular diseases-established risk factors for dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II randomized placebo‐controlled trial, a mast cell inhibitor added to standard care delayed cognitive decline in mild‐to‐moderate AD 30 . In a small cohort of asthma patients, leukotriene receptor antagonists decreased risk of dementia 31 …”
Section: Discussionmentioning
confidence: 99%
“…Stosowanie inhibitorów 5-LOX i FLAP hamuje akumulację Aβ w tkankach [114,118], natomiast antagoniści CysLT1R hamują aktywność TNF-α, IL-1β i szlaku NF-κB, co prowadzi do wyciszenia aktywności β-sekretazy oraz zmniejszenia stresu oksydacyjnego i poprawy funkcji poznawczych [73]. Działanie LTRA hamuje proces zapalny oraz zmniejsza przepuszczalność bariery krew-mózg, wobec czego mogą być one stosowane w przywracaniu prawidłowej funkcji i struktury układu nerwowego [117,119]. Blokowanie CysLT1R montelukastem lub pranlukastem może być skuteczne w leczeniu choroby Alzheimera przez zmniejszenie neurotoksyczności indukowanej Aβ, wyciszanie stanu zapalnego, hamowanie aktywności szlaków proapoptotycznych neuronów oraz poprawę funkcji poznawczych, przede wszystkim pamięci [116,119].…”
Section: Montelukastunclassified
“…Działanie LTRA hamuje proces zapalny oraz zmniejsza przepuszczalność bariery krew-mózg, wobec czego mogą być one stosowane w przywracaniu prawidłowej funkcji i struktury układu nerwowego [117,119]. Blokowanie CysLT1R montelukastem lub pranlukastem może być skuteczne w leczeniu choroby Alzheimera przez zmniejszenie neurotoksyczności indukowanej Aβ, wyciszanie stanu zapalnego, hamowanie aktywności szlaków proapoptotycznych neuronów oraz poprawę funkcji poznawczych, przede wszystkim pamięci [116,119]. Montelukast znajduje się II fazie badań klinicznych w leczeniu choroby Alzheimera, gdzie bada się jego potencjalne działanie nasilające wytwarzanie nowych neuronów, zmniejszające stan zapalny, poprawiające pamięć i funkcje poznawcze [73,120].…”
Section: Montelukastunclassified
“…Recent work using data from electronic health record databases worldwide has reported possible relationships between montelukast and neuropsychiatric events, such as sleeping disorders [ 7 ], depression [ 6 ], dementia [ 8 ] and attention deficit/hyperactivity disorder (ADHD) [ 9 ]. The largest observational study to date initiated by the FDA Sentinel Initiative revealed a reduced risk of outpatient depressive disorders [ 6 ], yet paediatric Canadian studies identified increased risk of neuropsychiatric events [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%